Liver dysfunction in patients with severe anorexia nervosa. Issue 2 (8th September 2015) - Rosen, Elissa; Sabel, Allison L.; Brinton, John T.; Catanach, Brittany; Gaudiani, Jennifer L.; Mehler, Philip S.
ABSTRACT: Objective: Evaluation of liver dysfunction in patients with severe anorexia nervosa (AN) has typically been limited to small case series. We report an investigation into the admission characteristics and clinical outcomes associated with liver dysfunction in a large cohort of adults hospitalized for medical stabilization of severe AN. Methods: We retrospectively evaluated electronic medical records to quantify the cumulative incidence of elevated aspartate aminotransferase (AST) and alanine aminotransferase (ALT). We compared mean (±SD), frequencies (%), and median (IQR) values of clinical covariates of interest by incidence of liver enzyme elevation. The study included 181 adults, admitted for medical stabilization of AN, from October 1, 2008 to December 31, 2013. Results: AST and ALT were mildly elevated in 27.6% of patients and severely elevated (more than three times the upper limit of normal) in 35.4% of patients. On admission, patients with severely elevated liver enzymes had a lower body mass index (BMI) (11.9 ± 1.8 kg/m 2 vs.13.3 ± 1.7 kg/m 2 ), lower percentage ideal body weight (56.5% ± 7.7% vs. 63.5% ± 8.3%), and lower prealbumin (64% vs. 37%) compared with the rest of the cohort ( p < 0.001). While hospitalized, patients with severely elevated liver enzymes more often developed hypoglycemia, hypophosphatemia, and experienced longer lengths of stay ( p < 0.001). Discussion: Elevated liver enzymes are common in our patient population with severe AN. Liver enzymes reached near normal values by the time of discharge. Severely elevated liver enzymes were associated with a lower BMI and the development of hypoglycemia. © 2015 Wiley Periodicals, Inc. (Int J Eat Disord 2016; 49:153–160).